Raman Spectroscopy Study of Chromium Deposition on La0.6Sr0.4Co0.2Fe0.8O3-δ Cathode of Solid Oxide Fuel Cells - Zhao, L.; Zhang, Jin; Becker, Thomas; Jiang, San Ping (The Electrochemical Society, Inc, 2014)
Chromium deposition and poisoning is one of the most fundamental issues affecting the performance stability of La0.6Sr0.4Co0.2Fe0.8O3-d (LSCF) perovskite electrode materials used in intermediate temperature solid oxide fuel cells (IT-SOFCs). In this work, the relationship between the surface segregation, Cr deposition and poisoning is studied using atomic force microscopy (AFM), confocal Raman microscopy and electrical conductivity relaxation method. The results indicate the segregation of SrO and Co3O4 phase on the LSCF surface after heat-treatment at 800°C. After exposed to Cr2O3 at 800°C in dry or wet air for 96 h, Cr deposition on LSCF surface preferentially takes place on the segregated SrO, forming the SrCrO4 phase. Humidity in air accelerates the surface segregation and formation of SrCrO4 on the LSCF surface. The present study provides unambiguous evidences that the segregated SrO plays a vital role in the nucleation and grain growth for the Cr deposition process. Cr deposition significantly deteriorates the surface exchange and diffusion processes for the O2 reduction reaction on LSCF electrodes.